The role of cnidarian developmental biology in unraveling axis formation and Wnt signaling - Holstein, Thomas W. (Developmental biology, 2022)
Cnidarians are fascinating creatures at the base of metazoan evolution possessing an almost unlimited regeneration capacity that has attracted the interest of researchers, from Abraham Trembley's discovery of regeneration to the present. They share a simple body plan and a high morphogenetic plasticity that has led to a broad spectrum of life cycles. With molecular genomics it became unequivocally clear that Cnidaria are the sister group of the Bilateria and how similar their molecular toolkit is to that of more complex animals. This has renewed interest in these simple animals, which have had an important role in the establishment of fundamental concepts for developmental biologists from the beginning. This review focuses on our current understanding of signaling centers (organizers) and morphogenetic gradients in cnidarians and how they relate to the emergence of the bilaterian body axes. The data are largely based on the cnidarian models Hydra and Nematostella and are supported by new studies on forms with a complete cnidarian life cycle, such as the medusozoans Aurelia and Clytia. Molecular studies on cnidarian development have revealed the existence of an ancient Wnt signaling center at the site of gastrulation, which was instrumental for the formation of a primary body axis and can be traced back to the common ancestor of bilaterian and non-bilaterian animals. New molecular data also suggest that the molecular vectors for the dorso-ventral and left-right body axis in bilaterians, Bmp and Nodal signaling, respectively, were already present but had different fates in the two clades. The close link of developmental processes in bilaterians and cnidarians but also their distinct differences make cnidarians an indispensable model for tackling fundamental questions in developmental biology from patterning, regeneration and other recent molecular approaches to theoretical concepts.
Available online 22 April 2022
Gesehen am 30.06.2022